2017
DOI: 10.1021/acsanm.7b00282
|View full text |Cite
|
Sign up to set email alerts
|

Stimulating the Visible-Light Catalytic Activity of Bi2MoO6 Nanoplates by Embedding Carbon Dots for the Efficient Oxidation, Cascade Reaction, and Photoelectrochemical O2 Evolution

Abstract: The present work demonstrates the facile synthesis and applications of carbon dots (CD)-embedded Bi2MoO6 nanoplates photocatalyst in the oxidative coupling of amines and oxidation of toluene and ethylbenzene. The synthetic protocol is applied to afford good yields of benzimidazole/benzothiazole via the cascade reaction between benzylamine and o-aminothiophenol/o-phenylenediamine. These photocatalytic reactions are performed under very mild conditions using the household light-emitting diode bulb as a light sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 82 publications
0
29
0
1
Order By: Relevance
“…Consequently, effective separation of photogenerated carriers and enhanced optical absorption were achieved, as shown in Figure b,c. Rajendra Srivastava's group observed that CDs could endow Bi 2 MoO 6 with higher stability and recyclability . As shown in Figure d,e, the CD decorated Bi 2 MoO 6 kept stable photocurrent even after 400 seconds rather than the descending one of pristine Bi 2 MoO 6 .…”
Section: Modulated Strategies Of Bi2moo6‐based Materials With Multifumentioning
confidence: 89%
See 2 more Smart Citations
“…Consequently, effective separation of photogenerated carriers and enhanced optical absorption were achieved, as shown in Figure b,c. Rajendra Srivastava's group observed that CDs could endow Bi 2 MoO 6 with higher stability and recyclability . As shown in Figure d,e, the CD decorated Bi 2 MoO 6 kept stable photocurrent even after 400 seconds rather than the descending one of pristine Bi 2 MoO 6 .…”
Section: Modulated Strategies Of Bi2moo6‐based Materials With Multifumentioning
confidence: 89%
“…Transient photocurrent responses of d) Bi 2 MoO 6 and e) 4CD/Bi 2 MoO 6 photoanodes. Reproduced with permission . Copyright 2017, American Chemical Society.…”
Section: Modulated Strategies Of Bi2moo6‐based Materials With Multifumentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous study showed that acidity plays an important role in the nal condensation step of tandem reactiond. 48,51,52 Therefore, the acidity of the materials was analyzed via NH 3 -TPD ( Fig. S4, ESI †).…”
Section: Physico-chemical Propertiesmentioning
confidence: 99%
“…This further combined with 4 to afford the desired product. The catalyst could be reused for five cycles consecutively .…”
Section: Nano‐transition Metal Catalyzed Oxidative Coupling Of O‐phenmentioning
confidence: 99%